Activated gliosis, accumulation of amyloid β, and hyperphosphorylation of tau in aging canines with and without cognitive decline - Hines, Amelia D.; McGrath, Stephanie; Latham, Amanda S.; Kusick, Breonna; Mulligan, Lisa; Richards, McKenzie L.; Moreno, Julie A. (Frontiers in Aging Neuroscience, 2023)
Canine cognitive dysfunction (CCD) syndrome is a well-recognized naturally occurring disease in aged dogs, with a remarkably similar disease course, both in its clinical presentation and neuropathological changes, as humans with Alzheimer’s disease (AD). Similar to human AD patients this naturally occurring disease is found in the aging canine population however, there is little understanding of how the canine brain ages pathologically. It is well known that in neurodegenerative diseases, there is an increase in inflamed glial cells as well as an accumulation of hyperphosphorylation of tau (P-tau) and amyloid beta (A1-42). These pathologies increase neurotoxic signaling and eventual neuronal loss. We assessed these brain pathologies in aged canines and found an increase in the number of glial cells, both astrocytes and microglia, and the activation of astrocytes indicative of neuroinflammation. A rise in the aggregated protein A1-42 and hyperphosphorylated tau, at Threonine 181 and 217, in the cortical brain regions of aging canines. We then asked if any of these aged canines had CCD utilizing the only current diagnostic, owner questionnaires, verifying positive or severe CCD had pathologies of gliosis and accumulation of A1-42 like their aged matched controls. However uniquely the CCD dogs had P-tau at T217. Therefore, this phosphorylation site of tau at threonine 217 may be a predictor for CCD.